The Taxation of International (non-resident) Sportspersons in South Africa - West, Craig (College of Accounting, 2014)
This thesis tests, firstly, the relevance of the OECD Model article 17 (the sportsperson article). Secondly, and accepting the current format of the sportsperson article in South African Double Tax Agreements (DTAs), the withholding tax applied to sportspersons performing in South Africa is analysed against the sportsperson article to determine whether these are appropriately aligned. The interpretational rules applicable to fiscal legislation in South Africa provide the methodology applied to the analysis of the withholding tax on sportspersons and the applicable DTA articles. Comparative analyses were conducted on all the South African DTAs in force at 1 June 2008 against the OECD, UN and USA Models. The OECD Model provides the core commentary as it is the general basis for most South African DTAs. Substantive analyses were conducted on the DTA articles of 'taxes covered' (OECD Article 2); sportspersons (OECD Article 17) and exchange of information (OECD Article 26). The scope of the withholding tax, both as regards persons and income, was found to be wider than that of the South Africa DTA sportsperson articles. This misalignment renders the withholding tax inapplicable in many cases when applied to a resident of a Contracting State. Naturally the misalignment has no influence on sportspersons from States that have not concluded a DTA with South Africa. The misalignment has also been replicated in the concessionary legislation promulgated for the 2009 FIFA Confederations Cup and 2010 FIFA World Cup in South Africa. As South Africa has not concluded DTAs with the bulk of the potential qualifying countries for the 2010 FIFA World Cup, the possibility of double taxation for sportspersons, support and auxiliary staff is increased. The difference in scope between the DTAs and the withholding tax is also an indicator of the increasing inappropriateness of the sportsperson article in current DTAs in force. While the initial justification for the article's inclusion may have been valid, in a global economy with business and individuals more mobile than national tax systems, an article focussed on only one class of mobile worker is inappropriate and lacks relevance. University of Cape Town Abstract iv As national governments react to global tax issues, development in exchange of information is bound to occur. However, to supplant withholding taxes in source States and to fully support the residence basis of taxation, regular (and reciprocal) exchange of information is required between States. Currently, differences in domestic tax systems and inefficiencies in exchanges render withholding taxes a necessary (albeit a crude) substitute to ensure that the income is taxed at least once between the source State and resident State. Advances in exchange of information are progressing rapidly and it is hoped that automatic relevant exchange of information in the future will remove the need for unnecessary withholding taxes and ensure that the right tax is levied on the right person in the appropriate State (Pocock, 2001). The South African withholding tax on sportspersons should be aligned with the sportsperson article in the interim (or a replacement article in the future). South Africa should also continue to actively pursue exchanges of information with other States and encourage other States to do so in global forums. It is recommended that the DTA sportsperson article be deleted and replaced with a more appropriate and relevant DTA article concerning all mobile individuals.